2022
DOI: 10.1111/aos.15241
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset glaucoma following congenital cataract surgery: Occurrence, visual acuity and risk factors: A 37‐year longitudinal follow‐up

Abstract: Purpose The aim of this study was to determine the prevalence of late‐onset glaucoma after surgery for congenital cataract in a cohort with long‐term follow‐up and to evaluate visual development following the diagnosis of postoperative glaucoma in comparison with no glaucoma development. Methods All children born between 1980 and 1997 in the western counties of Sweden who had undergone congenital cataract surgery were included (patients n = 77, eyes n = 122). Cataract was considered congenital if there was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…6,7 Reported frequency and risk factors for having GFCS vary according to study population, definition, and follow-up time, in a multitude of prospective and retrospective studies that have already been published on this topic. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Nonetheless, as reported in the Ninth Consensus Meeting of Childhood Glaucoma of the World Glaucoma Association, young age at the time of cataract surgery and microcornea consensually increase the risk of GFCS. 24 Typically, age <12 weeks at surgery is considered the critical timing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6,7 Reported frequency and risk factors for having GFCS vary according to study population, definition, and follow-up time, in a multitude of prospective and retrospective studies that have already been published on this topic. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Nonetheless, as reported in the Ninth Consensus Meeting of Childhood Glaucoma of the World Glaucoma Association, young age at the time of cataract surgery and microcornea consensually increase the risk of GFCS. 24 Typically, age <12 weeks at surgery is considered the critical timing.…”
Section: Discussionmentioning
confidence: 99%
“…24 These secondary glaucoma cases typically present an open angle 12,23,24 and develop in a bimodal pattern, either in the first year after surgery 16 or several years after surgery. 10,14 Recently, one study with a mean follow-up of 23 years after surgery reported a glaucoma prevalence of 15%, including late (10.7%) and early onset (4.1%), thus recommending life-long follow-up of all patients who have undergone surgery for congenital cataract in childhood. 10 Age at lensectomy is considered a significant modifier of the risk of development of GFCS after cataract surgery, 9,10,13,16,17,26 being the strongest marker of ocular "maturity."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations